ATTEMPTS TO TEACH THE RULES FOR BUILDING IMAGES PROJECTIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
A drawing is an image that allows you to restore the true shape and size of objects in the real world, drawn on a plane according to certain laws that are the apparatus of descriptive geometry. In the drawing, all sorts of issues related to the clay of buildings, ishoots and machines are solved. In this case, the creations performed on the drawing plane correspond to the corresponding apertures in space. Therefore, studying this subject develops a person's ability to visualize various objects.